A history of the British economy : 1740- 1970 - Murphy, Brian (London : Longman Group Ltd., 1973)
The book represents an eloquent attempt by a historian to keep the study in the company of the historians to whom it properly belongs. It provides a stimulating and comprehensive synthesis for the student of economic history
Part II of a survey covering the years 1086 - 1970
Includes bibliographical references and index.
osc 21/10/2019
Loans
Keywords: Economic history; Great Britain